Pemanfaatan Teknologi Berbasis Android Sebagai Media Deteksi Dini Tumbuh Kembang Balita - Rizkiyati, Ita (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Early detection of toddler growth is important to prevent developmental delays. This community service activity aims at improving parents’ knowledge in monitoring the growth of shrubs through an android app. Activity held on November 29, 2025 at Alkhairat Banawa kindergarten with participants 18 children and parents. Methods took the form of extensions, app usage training, as well as pre-test and post-test evaluations. Results showed improvement in parental knowledge and skills in early detection of growing toddler hemorrhoids.